2022
DOI: 10.1186/s13014-022-02169-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fractionated stereotactic radiotherapy on activity of daily living and performance status in progressive/recurrent glioblastoma: a retrospective study

Abstract: Background The prognosis of recurrent glioblastoma (GBM) is poor, with limited options of palliative localized or systemic treatments. Survival can be improved by a second localized treatment; however, it is not currently possible to identify which patients would benefit from this approach. This study aims to evaluate which factors lead to a lower Karnofsky performance status (KPS) score after fractionated stereotactic RT (fSRT). Methods We retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…[4] Moreover, in clinical practice, when managing recurrent glioblastoma, their performance status can significantly influence therapeutic decision-making, which may involve options like surgical re-intervention, re-irradiation, or best supportive care. [22] Due to the limited availability of publicly accessible, precise clinical databases, research predicting the course of performance status in patients with malignant tumors is much scarcer compared to the development of prediction models for overall survival or progression-free survival. However, in recent years, several studies have reported that machine learning approaches have successfully predicted changes in KPS 6 months postoperatively in patients with glioblastoma, as well as poor performance status in patients with cancer 6 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…[4] Moreover, in clinical practice, when managing recurrent glioblastoma, their performance status can significantly influence therapeutic decision-making, which may involve options like surgical re-intervention, re-irradiation, or best supportive care. [22] Due to the limited availability of publicly accessible, precise clinical databases, research predicting the course of performance status in patients with malignant tumors is much scarcer compared to the development of prediction models for overall survival or progression-free survival. However, in recent years, several studies have reported that machine learning approaches have successfully predicted changes in KPS 6 months postoperatively in patients with glioblastoma, as well as poor performance status in patients with cancer 6 months after diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment was described in a previous study conducted in our hospital [20], with fSRT delivered by a dedicated stereotactic radiation therapy machine (Cyberknife® (Accuray Inc.)), with 5 sessions of 5 Gy, distributed over 5-7 days, prescribed to the 80% normalized isodose line. The gross tumor volume (GTV) corresponded to the T1-enhanced lesion(s) on a recent brain MRI (maximum 4 weeks before treatment), matched with simulation computed tomography (CT).…”
Section: Methodsmentioning
confidence: 99%